PERAN MANAJEMEN KEUANGAN DALAM PENGADAAN SARANA DAN PRASARANA PENDIDIKAN DI MTs NEGERI 2 PRINGSEWU KECAMATAN BANYUMAS - Latifah, Latifah; Purwanti, Eri; Kusuma, Nurhadi (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
The research was conducted in MTs Negeri 2 Pringsewu because the researcher saw the lack of facilities and infrastructure in MTs Negeri 2 Pringsewu. The purpose of this study is to determine the implementation of financial management in the procurement of facilities and infrastructure. The method used in this research is descriptive qualitative. Sources of data in this study are principals, treasurers, facilities and infrastructure, TU and the entire board of teachers. The research instrument used in this research is interview, observation and documentation.The management of facilities and infrastructure at MTs Negeri 2 Pringsewu is done in various ways. Starting from planning, procurement, storage, inventory, maintenance and utilization. Referring to the results of the research, the authors provide advice for the principal to further improve the management of facilities and infrastructure, and for teachers to increase the use of media in teaching and learning process so that students can absorb the lesson well so that schools can improve the quality of education and realize the purpose of education.